Aktivitas Antioksidan, Kadar Air, Nilai pH dan Total Fenolik Dendeng Sapi yang di Curing Menggunakan Ekstrak Rosella (Hibiscus sabdariffa L.) - Elisa M.N Wete; Stefanus Sio; Kristoforus W. Kia (JAS, 2019)
This research has been carried out at the Widya Mandira Kupang Mipa Laboratory (UNWIRA), from February to April 2019. The material used in this study was 1 kg of thigh beef and 3 kg dried rosella petals (Hibiscus sabdariffa Linn). The method used is a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The treatments given are R0 = Beef + Spices, R1 = Beef + Spices + Nitrate 200 ppm, R2 = Beef + Spices + Rosella Extract 40%, R3 = Beef + Spices + Roselle Extract 60%. The purpose of this study was to determine what antioxidant value, water content, pH and total phenolic beef jerky after being cured using rosella extract, and to determine the effect of rosella extract as a natural antioxidant substitute for nitrate in curing beef jerky. Based on the results of this study it can be concluded that in the R3 sample with the addition of 60% roselle extract concentration can increase the total value of beef jerky phenolic value of 0.650 mg / g. And the addition of nitrate in the R1 sample was able to reduce the pH value and moisture content and increase the antioxidant value of beef jerky, for the beef jerky pH value was 5.3, and the water content value was 16.331%, the pH value and water content value was the best because it was in accordance with SNI . Thus it can be concluded also that samples with the addition of nitrate still play a more effective role compared to 40% and 60% rosella extract samples.